The Student’s Motivation in Learning Civic in Upper Secondary School Case Study: Phanluang Secondary School, Luang Prabang Province, The Academic Year 2018 - 2019 - SOULIVONG, Phetsamone; KHOTSAIGNOH, Saiphone; SIRIRATH, Khamphy; OUDOMSITH, Houmpheng; LIAMAHER, Yearher; KEOPASERTH, Dalyvone; SYVANKHAM , Sengduen; SIDAPHONE, Soulinthone (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research was intended to investigate the student’s motivation in learning civic in the upper secondary school case study: Phanluang secondary school, Luangprabang District, Luangprabang province. In the academic year 2018-209, the process is to survey with the quota sampling students in a total of 250 students who are studying in the upper class; the instrument of the study is a questionnaire with 4 part of items: personal reason, Teacher behavior, teaching process and learning environmental The descriptive statistics were used to analyze the data which included the Mean ( ), and Standard Deviation (SD) by using Microsoft Excel The research found that: The motivation to learn civic of the student at Phanluang upper secondary school was in the Median by the mean of = 2.967 and = 0.6 as the detail below - The personal reason factor: was in the Minimum by the mean of = 2.443; = 0.53 - the Teacher behavior factor: was in the Median by the mean of = 3.586; = 0.61 - The teaching process factor: was in the Median by the mean of = 2.499; = 0.73 - the environmental factor: was in the Median by the mean of = 2.891 ແລະ = 0.53 In addition, the compared mean of each factor is significantly different at .05 by the P-value = 0.015